2022
DOI: 10.3390/foods11020237
|View full text |Cite
|
Sign up to set email alerts
|

Propyl Gallate Treatment Improves the Postharvest Quality of Winter Jujube (Zizyphus jujuba Mill. cv. Dongzao) by Regulating Antioxidant Metabolism and Maintaining the Structure of Peel

Abstract: The quality and color of winter jujube fruits are easy to change after harvest. We studied the regulation mechanism of propyl gallate (PG) on post-harvest physiological quality of winter jujube, from the perspective of antioxidant metabolism and peel structure. In our research, winter jujube fruits were treated with 0.001 mol L−1 PG solution for 20 min. Our results showed that PG delayed the development of peel color, and improved the firmness, total soluble solids (TSS), and titratable acid (TA) of winter juj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Following previous methods [ 49 ] and modifying them, we rinsed the sample gently with distilled water to remove surface dirt and wiped it clean with a clean paper towel. Then, a clean and sterile scalpel was used to cut tomato peels (0.5 ~ 1.0 cm 2 ) at the equator, and attention was given to minimize pulling during sampling to avoid mechanical damage and affect the observation results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following previous methods [ 49 ] and modifying them, we rinsed the sample gently with distilled water to remove surface dirt and wiped it clean with a clean paper towel. Then, a clean and sterile scalpel was used to cut tomato peels (0.5 ~ 1.0 cm 2 ) at the equator, and attention was given to minimize pulling during sampling to avoid mechanical damage and affect the observation results.…”
Section: Methodsmentioning
confidence: 99%
“…According to a previously described method [ 49 , 50 ] with modifications, the sampling location of fresh tissue was determined. Samples were obtained between one and three minutes, and the size of the tissues was 1mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The color change is the most intuitive characteristic of the maturity and freshness of fresh-cut jackfruit, and it serves as an important parameter in consumer selection ( 35 , 36 ). During storage, the L* value of all samples consistently decreases while a* value, b* value, and ∆E steadily increase.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al . (2022) found that reducing LOX activity helped to maintain the peel structure and effectively improved the postharvest quality of jujube fruit by regulating antioxidant metabolism. In the present study, both 1‐MCP and LMF exerted a significant inhibitory effect on LOX activity, with their combined use producing a significantly superior inhibitory effect compared to the individual application of 1‐MCP or LMF.…”
Section: Discussionmentioning
confidence: 99%